EFFECTS OF ROSIN SIZING AGENT ON THE FIXATION OF BORON IN STYRAX TONKINENSIS WOOD - Thi Thanh Hien, Nguyen (Journal of Forestry Science and Technology, 2017)
The aim of this study was to evaluate the effect of rosin sizing agent upon fixing boron in Styrax tonkinensis (Piere) wood treated with mixtures of 3% boric acid and 1% rosin sizing agent. After treatment, wood samples were also analyzed by scanning electron microscope observation and energy-dispersive X-ray spectroscopy (SEM-EDX). The results showed that all boron-rosin formulations impregnated Styrax tonkinensis wood evenly penetrated into the wood blocks. Boron-rosin treatment decreased by 16% the amount of boron leaching from treated wood samples compared with those from the samples treated with boric acid alone. The SEM-EDX analysis proved that the boron element was still in the cell lumens of boron-rosin treated wood blocks after leaching. Results indicated that rosin emulsion sizing agent can have an effect on the fixation of boron in wood. This signifies that using of rosin as fixing agents may contribute to lead to wood treated with boron based preservatives being more widely used.